Motivators for adoption of photovoltaic systems at grid parity: A case study from Southern Germany. (March 2015) - Karakaya, Emrah; Hidalgo, Antonio; Nuur, Cali
Abstract: In some countries, photovoltaic (PV) technology is at a stage of development at which it can compete with conventional electricity sources in terms of electricity generation costs, i.e., grid parity. A case in point is Germany, where the PV market has reached a mature stage, the policy support has scaled down and the diffusion rate of PV systems has declined. This development raises a fundamental question: what are the motives to adopt PV systems at grid parity? The point of departure for the relevant literature has been on the impact of policy support, adopters and, recently, local solar companies. However, less attention has been paid to the motivators for adoption at grid parity. This paper presents an in-depth analysis of the diffusion of PV systems, explaining the impact of policy measures, adopters and system suppliers. Anchored in an extensive and exploratory case study in Germany, we provide a context-specific explanation to the motivations to adopt PV systems at grid parity.